Contesting Race and Citizenship : Youth Politics in the Black Mediterranean - Hawthorne, Camilla A. (Book collections on Project MUSE., 2022)
"Drawing on ethnographic and archival research, this book explores the political mobilizations of Black Italians, the children of African and Afro-Latinx immigrants who were born and raised in Italy, as they engage with questions of citizenship, state racism, and global Black diasporic interconnection"--